CARICOM Music Industry Development (CARMID) Project : interim report - Pereira, Beverley ([s.n.] [S.l.], 1998)
Focuses on the protection of music in CARICOM states. Looks at the status of copyright legislation and membership of international conventions. Examines the existing situation with regard to collective administration in CARICOM states.